The grandparents in the Matrix of Identity - Almeida Batista, Marcia (2020)
Based on her clinical experiences, the author presents the advantages of including grandparental figures in the exploration of the matrix of identity. Beyond allowing more flexibility than the direct investigation of parents-children relationships, this approach also gives us a clearer understanding of the changes that occur over time in social communication, of the ideology that is present in certain roles and how this influences the issues that clients bring to their therapy.